Equilibrium, kinetics and thermodynamics of hexavalent chromium biosorption on pristine and zinc chloride activated Senna siamea seed pods. Issue 4 (21st April 2019) - Ajmani, Abhishek; Shahnaz, Tasrin; Narayanan, Saranya; Narayanaswamy, Selvaraju
ABSTRACT: Hexavalent chromium contamination in water is an issue of huge concern due to its use at a high scale, toxicity and non-biodegradability. Biosorption is a cost effective and unconventional strategy for the elimination of Cr(VI). Here, a novel biosorbent Senna siamea seed pod biomass and its chemically activated form have been investigated for the elimination of hexavalent chromium from aqueous solution. The biosorbent was characterized by using BET, FTIR, FESEM-EDX and TGA techniques. Parameters controlling the biosorption process were optimized as pH 2.0, temperature 30°C, initial Cr(VI) concentration 500 mg/L, biosorbent dose 0.5 g/L. Optimized contact time was 210 and 180 min for pristine biomass and activated carbon, respectively. Langmuir isotherm correlated well with experimental data revealing that the biosorption occurred in monolayer pattern. Maximum biosorption capacity calculated by Langmuir biosorption isotherm was 119.18 and 139.86 mg/g for S. siamea pristine biomass and activated carbon, respectively. Pseudo-second order kinetic model correlated well with experimental data. Thermodynamic studies suggested that the biosorption process occurs in a non-spontaneous, stable and endothermic manner. These interesting findings on Cr(VI) biosorption by S. siamea seed pod biomass and S. siamea zinc chloride activated carbon vouches for its potential application as an unconventional biosorbent.